Evaluation of the lipid composition of the three lactation phases of raw, pasteurized and lyophilized pasteurized human milk (Research, Society and Development, 2020)
The aim of this study was to analyze the acidity, fatty acid (FA) composition and the triacylglycerol (TAGs) profile of human milk (HM) from three lactation phases (colostrum, transitional and mature) submitted to different treatments (raw milk, pasteurized, pasteurized in conjunction with lyophilization), in order to verify whether these processes applied to the samples can influence the characteristics of the analyzed components. To carry out the analyzes, the project was approved by the ethics committee and the HM was acquired at the Human Milk Bank (HMB) of the University Hospital of Maringá - HUM (Paraná, Brazil). The acidity analysis was performed using the titratable acidity method in Dornic degrees (ºD), the composition in FAs from Gas Chromatography with Flame Ionization Detector (GC-FID), and the TAGs profile by Mass Spectrometry with Electrospray Ionization source (ESI-MS). From the results obtained, it was possible to observe that the Dornic acidity and the composition in AGs did not undergo significant changes by the Tukey test (p